2021
DOI: 10.1186/s12998-020-00359-w
|View full text |Cite
|
Sign up to set email alerts
|

Skills, attitudes and uptake of evidence-based practice: a cross-sectional study of chiropractors in the Swedish Chiropractic Association

Abstract: Background Evidence-based practice (EBP) is integral to the delivery of high-quality health care. Chiropractic has been a licensed health profession in Sweden since 1989, but little is known of the uptake of EBP in this professional group. This study explored the self-reported skills, attitudes and uptake of EBP, and the enablers and barriers of EBP uptake, among licensed chiropractors in Sweden. Methods Licensed chiropractors (n = 172) of the Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 43 publications
16
31
0
Order By: Relevance
“…Included studies were heterogeneous in their survey methods. Seven studies used a postal mail-survey [ 22 , 23 , 25 , 26 , 30 , 31 , 34 ], four were electronically delivered [ 27 , 29 , 35 , 36 ], one used electronic and postal mail [ 33 ], and one used a combination of electronic and face-to-face distribution during a convention [ 24 ]. Two studies did not specify postal or electronic methods [ 28 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were heterogeneous in their survey methods. Seven studies used a postal mail-survey [ 22 , 23 , 25 , 26 , 30 , 31 , 34 ], four were electronically delivered [ 27 , 29 , 35 , 36 ], one used electronic and postal mail [ 33 ], and one used a combination of electronic and face-to-face distribution during a convention [ 24 ]. Two studies did not specify postal or electronic methods [ 28 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen reports were excluded (for reasons outlined in Fig. 1 ), resulting in a total of 39 studies (including 32 published studies 18 , 19 , 20 , 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 and 7 unpublished studies) 57 , 58 , 59 , 60 , 61 , 62 , 63 being included in this review.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…(2020) 40 1 1 1 1 1 1 1 NA NA NA 1 1 1 0 1 0.92 Leach et al. (2021) 41 1 1 1 1 1 1 1 NA NA NA 1 1 1 0 1 0.92 Roecker et al. (2013) 43 1 1 1 1 1 1 1 NA NA NA 0 0 1 0 1 0.75 Schneider et al.…”
Section: Resultsmentioning
confidence: 99%
“…As well as increasing understanding, the use of such guidance tools and resources has also been reported to increase perceived efficiency ( 74 ), which could help address the barrier of time constraints raised by participants. Insufficient time to implement evidence-based practice has been reported across public health settings ( 43 , 69 , 75 , 76 ) and is considered to significantly inhibit the uptake of new approaches ( 25 , 77 , 78 ). Participants suggested that providing protected time could help to overcome this and would enable teams to digest and implement new knowledge and skill development.…”
Section: Discussionmentioning
confidence: 99%